Penerapan Model Pembelajaran Cooperative Learning pada Pembelajaran Pendidikan Agama Islam - Azhura Farah Difa; Nahuda Nahuda (Departement of Mathematics Education, 2024)
This study discusses the importance of applying cooperative learning models to Islamic learning. In the 14th Jakarta State School of Education, several problems were found in the learning of Islamic religious education, such as a lack of understanding of important concepts, low motivation and active involvement, as well as inequality of participation. One of the models of learning that can be implemented, cooperative learning, which is interesting to use in Islamic education, is a model that emphasizes participatory collaboration, positive interaction, and task-sharing to create a conducive learning environment. To address this, a cooperative learning model is proposed as a solution. The research emphasizes the importance of integrating interactive learning methods that are relevant to the needs and conditions of current learners in order to improve educational outcomes. Overall, SMKN 14 Jakarta has successfully implemented the cooperative learning model for the learning of Islamic religious education, which shows that teachers can apply innovative and effective teaching methods with appropriate school support. SMKN 14 Jakarta can be an inspiring example for other schools that want to adopt a similar approach to improving the quality of their education and creating a more dynamic and inclusive learning environment.